MENGUKUR PENDIDIKAN INKLUSIF DALAM KESETARAAN GENDER: ANALISIS BIBLIOMETRIK DAN TINJAUAN PUSTAKA - Laurencia Vivin Monica; Yetri Hasan; Iqbal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Gender equality in inclusive education is a critical issue reflecting social justice and human rights. Although progress has been made in improving access to education, significant challenges persist, particularly in terms of educational quality, gender representation in leadership, and inclusion of marginalized groups such as children with special needs. This study aims to analyze the trends, topics, and research methods used in the study of inclusive education within the context of gender equality. Employing a qualitative approach, this research integrates bibliometric analysis and systematic literature review. Data were collected from various academic databases such as Scopus, Google Scholar, and Web of Science, and analyzed using VOSviewer software. The analysis focused on identifying the most cited articles, annual scientific productivity by country, keyword visualization (word cloud), and co-occurrence network mapping. Initial findings reveal a limited number of comprehensive studies addressing inclusive education from a gender perspective, with research concentrated in specific regions. Furthermore, author collaboration and policy-oriented studies on inclusive education remain insufficient. This study contributes to the body of knowledge on gender-responsive educational management and offers policy recommendations to support the development of a more equitable and inclusive education system. The results are expected to benefit scholars, education practitioners, and policymakers in fostering inclusive and gender-equal education practices.